2006
DOI: 10.1203/01.pdr.0000238326.42590.03
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Fetal Rat Lung Parathyroid Hormone-Related Protein Gene Regulatory Network Down-Regulates the Sonic Hedgehog/Wnt/βcatenin Gene Regulatory Network

Abstract: Lung development depends on endodermal Sonic Hedgehog (Shh) signaling to mesodermal Wingless/int/beta catenin (Wnt/␤catenin), followed by parathyroid hormone-related protein (PTHrP) signaling from endoderm to mesoderm. Fluid distension of fetal rat lung explants up-regulates PTHrP signaling and downregulates Shh/Wnt/␤catenin signaling, marked by decreases in Patched, Gli, Frizzled, and Dishevelled, inducing fibroblast triglyceride uptake, type II cell saturated phosphatidylcholine, and surfactant protein-B exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…It should not be surprising that RGZ stimulation of lipofibroblast differentiation would be cytoprotective against oxidant injury, since lipofibroblasts have intrinsic antioxidant properties, and they produce specific growth and differentiation factors that have both direct and indirect effects on alveolar differentiation and homeostasis (27,29,35). The uptake of neutral lipids by lipofibroblasts, which protects them against oxidant injury, is specifically dependent on PPAR-␥ induction of adipocyte differentiation-related protein, which determines the uptake and storage of neutral lipid (9,22).…”
Section: Discussionmentioning
confidence: 99%
“…It should not be surprising that RGZ stimulation of lipofibroblast differentiation would be cytoprotective against oxidant injury, since lipofibroblasts have intrinsic antioxidant properties, and they produce specific growth and differentiation factors that have both direct and indirect effects on alveolar differentiation and homeostasis (27,29,35). The uptake of neutral lipids by lipofibroblasts, which protects them against oxidant injury, is specifically dependent on PPAR-␥ induction of adipocyte differentiation-related protein, which determines the uptake and storage of neutral lipid (9,22).…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences are shown in supplementary material Table S2. Primers for other mRNAs were as reported previously: Wnt (Mohamed et al, 2004b), Fzds (Chen et al, 2004;Torday and Rehan, 2006), Ror2 (Mikels and Nusse, 2006) and LRP5/6 (Stump et al, 2003). PCR was performed using the program: 95°C for 3 minutes followed by 25-30 cycles of 95°C for 30 seconds, 51.1-61.5°C for 30 seconds, 72°C for 30 seconds with a final extension at 72°C for 5 minutes.…”
Section: Rna Isolation and Rt-pcr Analysismentioning
confidence: 99%
“…We have shown that during alveolarization, the formation of lung fluid upregulates the PTHrP signaling pathway in the endoderm, causing the downregulation of the Wnt/␤-catenin pathway (49), leading to the differentiation of the lipofibroblast. These cells dominate the alveolar acinus during fetal lung development but are highly apoptotic in the postnatal lung (3), giving rise to the alveolar septa (1).…”
Section: Myofibroblast Transdifferentiation As Evolution In Reversementioning
confidence: 99%